Cross-sectional phenotyping of small airway dysfunction in preschool asthma using the impulse oscillometry system. (4th May 2021) - Bokov, Plamen; Bafunyembaka, Gabriel; Medjahdi, Noria; Bernard, Agnès; Essalhi, Mohamed; Houdouin, Véronique; Peiffer, Claudine; Delclaux, Christophe
Abstract: Objective. Asthma is a chronic inflammatory airway disorder known to induce small airways dysfunction (SAD). It is important to develop tools to assess the presence and extent of SAD in daily clinical practice. An Impulse Oscillometry System (IOS) might detect SAD, but the validity of the underlying model (serial Resistive airway and Compliant tissue model: RC model) in diseased lungs remains questionable. Methods. Our objective was to evaluate the usefulness of parameters obtained from six electrical circuit models that were fitted to the measurements of impedance obtained with IOS in asthmatic children characterized by an abnormal lung function defined by an increased baseline interrupter resistance (Rint, z-score > +1.645). Results. The six models were tested in 102 asthmatic children (median age: 5.5 years). Two models allowed the description of 92/102 (90%) children: 74 by the extended RIC model (central and peripheral Resistance, Inertance and peripheral airway Compliance) and 18 by the Mead1969 model (extended RIC plus lung compliance). Thus, peripheral airway compliance and resistance were essential to describe lung function abnormalities of these asthmatic children. Parenchyma impairment (increased lung compliance) which was responsive to salbutamol was present in 18% of asthmatic children. After salbutamol, peripheral airway resistance decreased while peripheral airway compliance increased, arguing for asthma-related SAD. R5-20Hz independently correlated with the two latter parameters but was increased in two thirds of children with increased Rint only. Conclusion. Additional modeling of IOS results can be a reliable tool to assess the presence and extent of SAD in young asthmatic children.